Factors Affecting Access to Formal Credit by Micro and Small Enterprises in Uganda - Faisal Buyinza; Anthony Tibaingana; John Mutenyo (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2018)
This article investigates the factors affecting access to formal credit by micro and small enterprises in Uganda using the Gender Enterprise Survey that was funded by the IDRC. The study employed a probit model. The findings show that firm sales, owner's education level, belonging to a business association, belonging to business group, use of internet, owning a personal and business bank account, and gender of the owner are positively associated with access to formal credit. We also find that experienced firms are less likely to apply for credit hence reduce the probability to receive formal bank credit. Our results provide insights on the existing gaps in designing supportive policies for micro and small enterprise to enable them increase their access to credit especially from the formal financial institutions.
Keywords: 330; Credit constraint; micro and small enterprises; sample selection; Uganda